2010
DOI: 10.1038/ajg.2010.110
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance Predicts Rapid Virologic Response to Peginterferon/Ribavirin Combination Therapy in Hepatitis C Genotype 4 Patients

Abstract: IR is a major determinant of both RVR and SVR in genotype 4 CHC patients. HOMA-IR would seem to be a useful tool for predicting the response to therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 24 publications
4
63
0
Order By: Relevance
“…29,30 Insulin resistance and baseline HCV viral loads have also been noted to predict RVR in patients with HCV-4 infection. 31 Mangia et al 32 showed that a high dose of ribavirin and low pretreatment HCV viral loads with an HCV-2 infection were independent factors predicting RVR in patients with HCV-2/HCV-3 infection. 32 However, little is known about the general relevance of host genetics to the early phases of viral kinetics in the treatment of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Insulin resistance and baseline HCV viral loads have also been noted to predict RVR in patients with HCV-4 infection. 31 Mangia et al 32 showed that a high dose of ribavirin and low pretreatment HCV viral loads with an HCV-2 infection were independent factors predicting RVR in patients with HCV-2/HCV-3 infection. 32 However, little is known about the general relevance of host genetics to the early phases of viral kinetics in the treatment of HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…The association between chronic HCV infection and increased prevalence of IR and type 2 diabetes mellitus (DM) was extensively reported [4]. IR was reported to accelerate fibrosis in chronic HCV-infected patients [5,6], which may lead to increased risk of cirrhosis and hepatocellular carcinoma [7] and has been associated with reduced rate of sustained virological response (SVR) in response to pegylated interferon (IFN)-α and ribavirin therapy [8]. …”
Section: Introductionmentioning
confidence: 99%
“…There was a statistically significant difference comparing the HOMA-IR of patients achieving complete early virological response, partial early virological response and non-response (P = 0.006). Likewise, Khattab et al found a highly and significant relationship between insulin resistance and treatment response (P < 0.001) (25). Similarly, Moucari et al concluded from their study that HO-MA-IR score < 2 was associated with early virological response (P < 0.001) and also remained an independent predictor of sustained virological response by multiple logistic regression analysis (P = 0.03) (23).…”
Section: Discussionmentioning
confidence: 89%
“…End-of-treatment response was defined as serum HCV-RNA below the limit of detection at the end of treatment. We considered non-responders to be: patients with no or minimal change in their HCV-RNA titres (< 2 log10 drop at week 12 as compared with baseline); those with viral load drop > 2 log10 at week 12 as compared with baseline and who still had positive HCV-RNA at week 24; those who became HCV-RNA positive after negativization before the end of treatment (breakthrough response); and those who became HCV-RNA positive after negativization at the end of treatment (25).…”
Section: Virological Assessmentsmentioning
confidence: 99%